(untitled) (Research, Society and Development, 2021)
In the transitional phase of adolescence, the literature shows that self-esteem and social skills are associated with mental health, development and better social adaptation. Considering this relation, the goal of the present research was to evaluate the effect of a Social Skills Training in promoting self-esteem in adolescents. Ten adolescents aged from 13 to 15 took part in an intervention in the pre and post testing scenarios. The assessment measures applied at both pre and post scenarios were Rosenberg Scale, Inventory of Social Skills for Adolescents – IHSA-Del-Prette, Field Notebooks and Initial and Final Questionnaires. The quantitative data were analyzed using the SPSS software and the qualitative data were classified into thematic categories, analyzed and used to illustrate the quantitative results. The quantitative and qualitative results indicated that the Social Skills Training was effective in increasing self-esteem in adolescents, especially in improving self-control and assertive skills. It was concluded that the research realized demonstrated that the Social Skills Training is a relevant instrument for the promotion of self-esteem in adolescents.